Financial Literacy of Youth in Indonesia - Sari, Ambar Mawar; Saudi, Mohd Haizam Mohd; Razimi, Mohd Shahril Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The current study focuses on Indonesian youth in terms of the levels of financial literacy which is an important aspect of planning for future needs. The rationale behinds this would be lack of such knowledge, as well as skills, leads to poor money management and decision making. Acquiring literacy in finance leads to the ability to make informed judgments and have efficient decisions about use and management of money. Furthermore, individuals lacking such knowledge leads to poor discipline in controlling individual finances which makes them susceptible to poor debt management especially among the youth. Thus, the current research aims to identify determinants of financial literacy among youth in Indonesia as it influences their financial wellbeing in the short- and long-term. Findings indicate support of empirical priors and thus allows the recommendation of emphasis on financial education, encouragement towards a positive attitude for money attitude as well as utilization of financial socialization agents in order to improve financial literacy among youth in Indonesia.